Numerical Modeling of Permeable Floating Breakwater under the Action of Waves - Cao, Yufen; Shi, Yang; Bai, Yuchuan; Li, Shaowu; Chen, Hanbao; Yang, Huili (Journal of coastal research, 2018)
Cao, Y.F.; Shi, Y.; Bai, Y.C.; Li, S.W.; Chen, H.B., and Yang, H.L., 2018. Numerical modeling of permeable floating breakwater under the action of waves. In: Shim, J.-S.; Chun, I., and Lim, H.S. (eds.), Proceedings from the International Coastal Symposium (ICS) 2018 (Busan, Republic of Korea). Journal of Coastal Research, Special Issue No. 85, pp. 1101–1105. Coconut Creek (Florida), ISSN 0749-0208. Floating breakwaters are commonly used to protect shorelines, marine structures and harbors from wave attacks. This paper studies the interaction of water wave with a hinged permeable multi-tube floating structure, using a numerical model based on the Navier-Stokes (NS) solver and smoothed particle hydrodynamics (SPH) method. The simulation is performed in a 2D numerical wave tank (NWT) equipped with an active absorbing wave maker and a sponge layer. The motion of the multi-module floating structure is driven by hydrodynamic force and mooring force with its buoy structure being permeable. The dynamic boundary method is adopted to calculate the hydrodynamic force, and a light spring model is employed to calculate the mooring force. A laboratory experiment is conducted to validate the numerical model. The validated model is then employed to investigate the hydrodynamic characteristics of floating breakwater with different mooring type and structural style subject to various waves. The effects of wave condition, relative water depth on wave transmission are investigated. It is found that wave period have significant effect on transmission coefficient.